Engineered polysaccharide alpha‐1, 3 glucan as isocyanate‐reactive component in viscoelastic polyurethane foams. Issue 10 (11th October 2020) - Lenges, Christian; Behabtu, Natnael; Mok, Jorge; Sendijarevic, Ibrahim; Sendijarevic, Aisa
Abstract: Enzymatic polymerization is emerging as scalable method to convert sucrose to engineered polysaccharides. Polymer architecture and material properties can be controlled selectively to produce novel differentiated biomaterials. One first example for such an engineered polysaccharide is alpha‐1, 3‐polyglucose (alpha‐1, 3‐glucan) synthesized using glucosyltransferase (GTF) enzymes. Stable dispersions of alpha‐1, 3‐glucan in polyether polyols were prepared with narrow particle size distributions, which are reactive with isocyanate allowing for covalent bonding to the hard segment of the polyurethane polymer matrix. This study further explored the use of alpha‐1, 3‐glucan (PS) in the preparation of viscoelastics (VE) polyurethane foams. The introduction of alpha‐1, 3‐glucan into the polyurethane polymer matrix was found to increase the load‐bearing properties of VE foams without impacting the density. Other key performance properties of VE foams were effectively unchanged, including resilience, tensile, and tear strength. Cell size and morphology were also unaffected. The glass transition of these VE foams was not impacted; however, the overall thermal dimensional stability was improved as considerable reduction in compression set was observed. The results of this study indicated that alpha‐1, 3‐glucan disperses in polyether polyols to improve performance characteristics of the VE foams, as well as other flexible polyurethane foams properties. Abstract :